Development of a micromixing system for treatment of ORL 48 microtissues in different concentrations of cytochalasin B - Sundra, Sargunan (2018)
Mixing and dilution are essential procedures in pharmaceutical operation to process two or more components in a separate or thoroughly mixed condition until homogenous solution was obtained. However, conventional serial dilution method used in laboratory assessment causes high usage of reagents, higher complexity procedures and costly. Micromixing method provides a better platfonn that enables mixing and dilution of liquid-based reagents which is convenient solutions preparation, easy liquid handling and time-saving. In this study, a polydimethylsiloxane (PDMS) micromixer was designed, simulated and prototyped using vinyl tape method and successfully applied to mix and dilute Cytochalasin-B in culture media (CB-DMEM, 30.0 µM) with 0.05 % ethanol solutions (diluent) to produce four different concentrations of CB-DMEM (5.3, I 0.6, 14.8, and 20.2 µM). The different concentrations of CB-DMEM were applied on to ORL-48 microtissues produced by using flicking technique. The morphological responses, cell viability and cell proliferation of ORL-48 monolayer cells (2D) and microtissues (3D) treated in four different CB concentrations were assessed via phase contrast microscopy, live/dead staining and Alamar Blue® staining respectively. The results show that both 2D and 30 of ORL-48 microtissues were only morphologically affected (fibroblastic spreading to round shape) while cell viability and cell proliferation show that CB treatment solely does not causes apoptosis (:::::: 90 % cells are alive and able to proliferate). The micromixer employed in solution preparation of CB-DMEM (5.3, 10.6, 14.8, and 20.2